Oncological and Functional Outcomes of Transoral Robotic Surgery and Endoscopic Laryngopharyngeal Surgery for Hypopharyngeal Cancer: A Systematic Review - Lai, Katherine W. K.; Lai, Ronald; Lorincz, Balazs B.; Wang, Chen-Chi; Chan, Jason Y. K.; Yeung, David C. M. (Frontiers in Surgery, 2022)
Objectives Hypopharyngeal carcinoma (HPC) is a head and neck carcinoma with poor prognosis. Traditional laryngopharyngectomy offered promising oncological outcomes at the cost of functional outcomes. The recent advent in transoral robotic surgery (TORS), an organ preserving surgery, has opened up new perspectives in the treatment for hypopharyngeal carcinoma. Here we evaluate minimally invasive organ preservation surgery for HPC in terms of feasibility, oncological and functional outcomes. Methods Six databases (CUHK Full Text Journals, Embase 1910 to 2021, Ovid Emcare, Ovid MEDLINE(R), CINAHL, Pubmed) were searched for articles and primary studies for transoral robotic surgery (TORS) and endoscopic laryngopharyngeal surgery (ELPS) for hypopharyngeal carcinoma. Screening was completed using predefined inclusion/exclusion criteria. Results A total of 8 studies on TORS and 3 studies on ELPS were eventually chosen after full text review. For studies on TORS, 69.3% of patients (95 out of 137) still survived at the last follow up with a mean follow up time of 23.20 months (range: 12.8-37.21 months). Severe intraoperative and postoperative complications have not been reported. No cases of TORS required a conversion to open surgery. Swallowing function was optimal post operatively with only 6 patients eventually required a percutaneous endoscopic gastrostomy (PEG) for feeding. Disease specific survival was taken as the parameter for measurement of oncological outcomes. 2 studies reported a disease specific survival of 100% within their follow up period of 1 and 1.5 year respectively. Another 2 studies reported a 2 year DSS of 89% and 98%. A 5 year DSS of 100% in early stage and 74% in late stage were achieved in one study. Another study also reported a 5 year DSS of 91.7%. For studies of ELPS, a 5 year and 3 year disease specific survival of 100% were achieved in 2 studies. Patients who underwent ELPS had good post operative swallowing function with no PEG placement. There were also no other fatal complications. Conclusions TORS and ELPS for HPC provide satisfactory long term oncological and functional outcomes, improving post operative quality of life of patients.